Ecofriendly hydrogen production from abundant hydrogen sulfide using solar light-driven hierarchical nanostructured ZnIn2S4 photocatalyst - Chaudhari, Nilima S.; Bhirud, Ashwini P.; Sonawane, Ravindra S.; Nikam, Latesh K.; Warule, Sambhaji S.; Rane, Vilas H.; Kale, Bharat B. (Green Chemistry, 2011)
It is quite well-known that refineries are producing huge amount of H2S which has been used to produce sulphur and water using the well-known Claus process. This process is not an economically viable process, due to the high-cost chemical process and creates further acute environmental problems. Therefore, we have demonstrated the conversion of poisonous H2S into H-2 using an ecofriendly phocatalysis process which is a green unconventional energy source. We have investigated ecofriendly nanostructured ZnIn2S4 photocatalyst to produce hydrogen from H2S using solar light. We also demonstrate the controlled synthesis of hierarchical nanostructured ZnIn2S4 using a facile hydrothermal method. The morphologies obtained have been greatly influenced by the presence of triethylamine (TEA) with various concentrations during the reaction. Surprisingly, a highly crystalline hexagonal layer structured ZnIn2S4 was obtained instead of cubic spinel. The hierarchical nanostructure, i.e. marigold flower-like morphology, was obtained without any surfactant. The thin and transparent petals self-assembled to form the unique nanostructured marigold flower. The highly crystalline puffy marigold flowers and nanoplates/nanostrips were obtained using TEA-assisted hydrothermal synthesis. Optical study shows the band gap in the range of 2.34-2.48 eV. Considering the band gap in the visible region, ZnIn2S4 is used as photocatalyst for hydrogen production from hydrogen sulphide under solar light which is hitherto unattempted. The constant photocatalytic activity of hydrogen evolution, i.e. 5287 mu mol h(-1), was obtained using such hierarchical nanostructured ZnIn2S4 under visible light irradiation. It is noteworthy that the H-2 evolution rate obtained is much higher compared to earlier reported photocatalysts. Considering the significance of morphologies for photocatalytic application, the formation mechanism has also been furnished. The unique hierarchical nanostructured ZnIn2S4 ternary semiconductor having hexagonal layer will have potential applications in solar cells, LEDs, charge storage, electrochemical recording, thermoelectricity and other prospective electronic and optical devices.

Organization of cubic CeO2 nanoparticles on the edges of self assembled tapered ZnO nanorods via a template free one-pot synthesis: significant cathodoluminescence and field emission properties - Warule, Sambhaji S.; Chaudhari, Nilima S.; Kale, Bharat B.; Patil, Kashinath R.; Koinkar, Pankaj M.; More, Mahendra A.; Murakami, Ri-ichi (Journal of Materials Chemistry, 2012)
The present investigation explores the controlled architecture of a CeO2-ZnO nanocomposite via a template-free, low temperature, facile single step solvothermal approach. This complex architecture depicts cubic single crystalline CeO2 nanoparticles (size similar to 15 nm) grown on the edges of tapered ZnO nanorods with definite orientations and alignments. The formation of wurtzite ZnO, cubic CeO2 and the coexistence of Ce3+ and Ce4+ on the surface of the CeO2-ZnO nanocomposites are confirmed using various characterization tools. The finding of such unique nanostructures by a facile method is exemplified by a plausible growth mechanism. Surprisingly, the aqueous mediated ultrasonication reaction conferred the formation of crystalline ZnO nanotubes of diameter similar to 50 nm. Spatially resolved cathodoluminescence spectra are obtained by linearly scanning an individual CeO2-ZnO nanorod along its length, which reveals the size-dependent surface effects. Interestingly, such hybrid CeO2-ZnO nanoarchitecture is observed to exhibit enhanced field emission properties, demonstrating better current stability as compared to other ZnO nanostructures. This is attributed mainly to strong surface interactions between the Ce-ionic species and the ZnO nanorods. Herein, a soft-chemical approach is used for the first time to architect a binary oxide nanostructure, which is otherwise accomplished using high temperature techniques, as reported elsewhere. Also, the present work not only gives insight into understanding the hierarchical growth behaviour of the CeO2-ZnO nanocomposite in a solution phase synthetic system, but also provides an efficient route to enhance the field emission performance of ZnO nanostructures, which could be extended to other potential applications, such as chemical sensors, optoelectronic devices and photocatalysts.

Controlled synthesis of aligned Bi2S3 nanowires, sharp apex nanowires and nanobelts with its morphology dependent field emission investigations - Warule, Sambhaji S.; Chaudhari, Nilima S.; Kale, Bharat B.; Pandiraj, S.; Khare, Ruchita T.; More, Mahendra A. (Crystengcomm, 2013)
Well-aligned ultra-long Bi2S3 nanowire arrays with three kinds of apex morphology - abruptly sharpened apex, thin belt and flat - have been systematically fabricated on tungsten (W) foil by a facile hydrothermal method. The structural and morphological studies reveal formation of distinct tip morphologies, possessing high aspect ratio, single crystalline nature and growth along the orthorhombic [001] axis. A plausible growth mechanism has been proposed on the basis of observed experimental results. The field emission properties of Bi2S3 nanowires and sharp apex Bi2S3 nanowires are investigated. From the field emission studies, the values of the turn-on field, required to draw emission current density of similar to 0.1 mu A cm(-2), are observed to be similar to 2.01 and 1.21 V mu m(-1) for nanowires and sharp apex nanowires, respectively. Furthermore, ultra-long Bi2S3 nanowires are also grown on the W microtip (brush-like) from which very high emission current density similar to 11 mA cm(-2) has been drawn. These results are helpful for the design, fabrication and optimization of integrated field emitters using 1D nanostructures as cold cathode material.

Decoration of CdS nanoparticles on 3D self-assembled ZnO nanorods: a single-step process with enhanced field emission behaviour - Warule, Sambhaji S.; Chaudhari, Nilima S.; Shisode, Raju T.; Desa, Keith V.; Kale, Bharat B.; More, Mahendra A. (CrystEngComm, 2015)
A well-defined CdS-ZnO heteroarchitecture has been synthesized via a facile single-step hydrothermal approach. The morphological and structural studies reveal the formation of 3D nano-architectures, in which self-assembled ZnO nanorods (diameter similar to 50 nm) are well decorated with single crystalline CdS nanoparticles (size similar to 10 nm). The CdS-ZnO heteroarchitecture exhibits a remarkable change in the optical absorption due to the surface modification of ZnO nanorods by CdS. Surprisingly, under identical reaction conditions, the global ZnS nanoparticles are selectively grown at the apex of ZnO nanorods on the Zn substrate. Furthermore, a plausible growth mechanism has been presented on the basis of experimental results. Interestingly, the CdS-ZnO heteroarchitecture shows enhanced field emission properties such as low turn-on field, high emission current density and better current stability in comparison to other ZnO-based nanostructures. The present CdS-ZnO heteroarchitecture could be extended to other potential applications, such as chemical sensors, photodetectors, optoelectronic devices, and photocatalysts.

Enhanced field emission behaviour from ethylene glycol mediated synthesis of 2D hexagonal SnS2 disc with nanoparticle - Mutadak, Pallavi R.; Chaudhari, Nilima S.; Gadhave, Dattatraya C.; Rajput, Parikshit K.; Kolekar, Sadhu K.; Late, Dattatray J.; More, Mahendra A.; Warule, Sambhaji S. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Herein, octahedron and stacked 2D hexagonal disc - like nanostructures of SnS2 were obtained by hydrothermal and ethylene glycol mediated hydrothermal methods, respectively. Attempt has been made to shade light on the plausible growth mechanism. Liquid phase exfoliation followed by centrifugation process leads to presence of tiny single crystalline SnS2 nanoparticles (similar to 5 nm) on the hexagonal discs over C substrate, characterized by preferred growth along {001} direction. The observed Raman shift and enhanced intensities of A(1g) and E-g modes infer charge interactions between the SnS2 disc and C substrate. Interestingly, the SnS2-C emitter exhibited superior field emission (FE) behaviour due to the unique morphology, excellent charge transfer, and reduced work function (similar to 4.1 eV). Here the extraction of large current density of similar to 1137 mu A/cm(2) at an applied field of 3.72 V/mu m, with good emission current stability. The present strategy is beneficial to design architectured morphology for multi-functionality.
Keywords: 2D layered materials; Field Emission (FE); SnS2; SnS2 on C